2019
DOI: 10.1111/acel.13016
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of cellular NAD+ by NQO1 enzymatic action improves age‐related hearing impairment

Abstract: Age‐related hearing loss (ARHL) is a major neurodegenerative disorder and the leading cause of communication deficit in the elderly population, which remains largely untreated. The development of ARHL is a multifactorial event that includes both intrinsic and extrinsic factors. Recent studies suggest that NAD+/NADH ratio may play a critical role in cellular senescence by regulating sirtuins, PARP‐1, and PGC‐1α. Nonetheless, the beneficial effect of direct modulation of cellular NAD+ levels on aging and age‐rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…However, no differences were observed in Pgc1α or its downstream targets Nrf1 and Tfam . As recently reported by (Kim et al, 2019), enhanced Sirt1 expression could limit PARP1 activation by decreasing the NAD + pool in the 3‐ and 9‐month‐old G6PD ‐Tg cochleae.…”
Section: Discussionsupporting
confidence: 66%
“…However, no differences were observed in Pgc1α or its downstream targets Nrf1 and Tfam . As recently reported by (Kim et al, 2019), enhanced Sirt1 expression could limit PARP1 activation by decreasing the NAD + pool in the 3‐ and 9‐month‐old G6PD ‐Tg cochleae.…”
Section: Discussionsupporting
confidence: 66%
“…The rats in the simulated ageing groups accumulated more MDA than those in the corresponding control groups, and GSH content and SOD activity demonstrated opposite change trends. Many previous studies have indicated that oxidative stress is closely related to the occurrence and development of central presbycusis, consistent with the results of our study [53][54][55]. ROS destroy cell function, destroy normal tissues and cells and affect normal osmotic pressure, further leading to metabolic disorders of important organs and eventually to overall ageing [56][57][58].…”
Section: Discussionsupporting
confidence: 91%
“…337,344,345 Augmentation of NAD + by β-lap, a potent substrate of NQO1, effectively prevents ARHL and its accompanying harmful effects by preventing oxidative stress and inflammation and improving mitochondrial function in rodents. 346 Moreover, mounting evidence has shown that NAD + -dependent sirtuins can extend the lifespan of yeast, worms, flies and mice and alleviate many diseases of aging-related pathologies. For instance, both brain-specific or whole-body SIRT1-overexpressing transgenic mice exhibit a slowed aging and a prolonged lifespan.…”
Section: Abnormal Nad + Metabolism In the Pathophysiological Conditionmentioning
confidence: 99%